Regulation of Wheat Seed Dormancy by After-Ripening Is Mediated by Specific Transcriptional Switches That Induce Changes in Seed Hormone Metabolism and Signaling - Liu, Aihua (Public Library of Science, 2013)
Treatments that promote dormancy release are often correlated with changes in seed hormone content and/or sensitivity. To understand the molecular mechanisms underlying the role of after-ripening (seed dry storage) in triggering hormone related changes and dormancy decay in wheat (Triticum aestivum), temporal expression patterns of genes related to abscisic acid (ABA), gibberellin (GA), jasmonate and indole acetic acid (IAA) metabolism and signaling, and levels of the respective hormones were examined in dormant and after-ripened seeds in both dry and imbibed states. After-ripening mediated developmental switch from dormancy to germination appears to be associated with declines in seed sensitivity to ABA and IAA, which are mediated by transcriptional repressions of PROTEIN PHOSPHATASE 2C, SNF1-RELATED PROTEIN KINASE2, ABA INSENSITIVE5 and LIPID PHOSPHATE PHOSPHTASE2, and AUXIN RESPONSE FACTOR and RELATED TO UBIQUITIN1 genes. Transcriptomic analysis of wheat seed responsiveness to ABA suggests that ABA inhibits the germination of wheat seeds partly by repressing the transcription of genes related to chromatin assembly and cell wall modification, and activating that of GA catabolic genes. After-ripening induced seed dormancy decay in wheat is also associated with the modulation of seed IAA and jasmonate contents. Transcriptional control of members of the ALLENE OXIDE SYNTHASE, 3-KETOACYL COENZYME A THIOLASE, LIPOXYGENASE and 12-OXOPHYTODIENOATE REDUCTASE gene families appears to regulate seed jasmonate levels. Changes in the expression of GA biosynthesis genes, GA 20-OXIDASE and GA 3-OXIDASE, in response to after-ripening implicate this hormone in enhancing dormancy release and germination. These findings have important implications in the dissection of molecular mechanisms underlying regulation of seed dormancy in cereals.